KOMUNIKASI KETERBUKAAN DIRI ORANG DENGAN HIV/AIDS (ODHA) MELALUI PLATFORM MEDIA SOSIAL YOUTUBE - Daniel Panogari; Yanuar Luqman; Nurul Hasfi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The issue of HIV/AIDS continues to be discussed in Indonesia. Especially with the stigma that attacks people living with HIV/AIDS (PLWHA) one-sidedly, many of them limit communication and close themselves off from interacting with society that discriminates against them. In fact, good relationships enable the social acceptance and support that PLWHA need from the community. In the midst of this negative stigma, there are a number of PLWHA who are able and successful to open themselves up at the community level on YouTube social media on third party channels which already have a large audience so that they are able to reach a wide and diverse society and challenge this negative stigma. For this reason, this research was conducted with the aim of describing PLWHA's communication of self-disclosure through third party YouTube channel videos based on their personal experiences. This research uses a qualitative research method with a phenomenological approach, an interpretive paradigm through data collection techniques in depth interviews with 3 informants with different personal backgrounds and experiences. The results of this research reveal a description of how communication strategies are prepared, considerations for managing and disclosing personal information, and the boundaries applied to this personal information, along with the turbulence experienced. The research uses the Communication Privacy Management theory by Sandra Petronio, which shows the results that there are differences in the communication strategies prepared by each PLWHA, and how they manage disclosure and personal boundaries based on various considerations related to cultural criteria, gender, motivation, context , and benefit-risk. The research also revealed new findings related to the responses received by PLWHA based on comparisons of intentions and self-disclosure activities that had previously been carried out. This self-disclosure activity provided results showing that the communication carried out was considered satisfactory because the positive response was in accordance with the initial goals and hopes of PLWHA, namely building relationships with the community; fighting stigma, educating the public, and motivating other PLWHA.